Scope for genetic rescue of an endangered subspecies though re-establishing natural gene flow with another subspecies - Harrisson, Katherine A.; Pavlova, Alexandra; Gonçalves da Silva, Anders; Rose, Rebecca; Bull, James K.; Lancaster, Melanie L.; Murray, Neil; Quin, Bruce; Menkhorst, Peter; Magrath, Michael J. L.; Sunnucks, Paul (Molecular ecology, 2016)
Genetic diversity is positively linked to the viability and evolutionary potential of species but is often compromised in threatened taxa. Genetic rescue by gene flow from a more diverse or differentiated source population of the same species can be an effective strategy for alleviating inbreeding depression and boosting evolutionary potential. The helmeted honeyeater Lichenostomus melanops cassidix is a critically endangered subspecies of the common yellow‐tufted honeyeater. Cassidix has declined to a single wild population of ~130 birds, despite being subject to intensive population management over recent decades. We assessed changes in microsatellite diversity in cassidix over the last four decades and used population viability analysis to explore whether genetic rescue through hybridization with the neighbouring Lichenostomus melanops gippslandicus subspecies constitutes a viable conservation strategy. The contemporary cassidix population is characterized by low genetic diversity and effective population size (Ne < 50), suggesting it is vulnerable to inbreeding depression and will have limited capacity to evolve to changing environments. We find that gene flow from gippslandicus to cassidix has declined substantially relative to pre‐1990 levels and argue that natural levels of gene flow between the two subspecies should be restored. Allowing gene flow (~4 migrants per generation) from gippslandicus into cassidix (i.e. genetic rescue), in combination with continued annual release of captive‐bred cassidix (i.e. demographic rescue), should lead to positive demographic and genetic outcomes. Although we consider the risk of outbreeding depression to be low, we recommend that genetic rescue be managed within the context of the captive breeding programme, with monitoring of outcomes.